Gwiezdny czas : "Wiary i winy" dalszy ciag - Kuron, Jacek (Londyn : "Aneks", 1991)
A second volume in the autobiographical notes and reflections by the leading politician who participated in the fall of Communism in Poland.
"Gwiezdny czas. Tom II wspomnien"--T.p. verso.
Title on verso t.p.: The Starry time.
Keywords: Kuron, Jacek; Dissenters -- Poland -- Biography; Poland -- Politics and government -- 1945-1980.; Poland -- Politics and government -- 1980-1989.